2020
DOI: 10.2147/ott.s237559
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knockdown of lncRNA <em>PCAT6</em> Enhances Radiosensitivity in Triple-Negative Breast Cancer Cells by Regulating<em> miR-185-5p</em>/<em>TPD52</em> Axis</p>

Abstract: Background: Long non-coding RNAs (lncRNAs) have been reported to play essential roles in regulating the radiosensitivity of cancers. Prostate cancer-associated transcript 6 (PCAT6) exerts oncogenic roles in several tumors. However, the roles of PCAT6 and its underlying mechanism in regulating the radiosensitivity of triple-negative breast cancer (TNBC) have not been investigated. Methods: The expression levels of PCAT6, microRNA-185-5p (miR-185-5p) and tumor protein D52 (TPD52) were determined by quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Lv et al (40) showed that PCAT6-overexpression promotes cell proliferation, migration, invasion and reduces apoptosis through the activation of the Wnt/β-catenin pathway in cervical cancer. Other studies have demonstrated that knockdown of PCAT6 reverses chemoresistance of cancer cells to 5-fluorouracil and enhances radiosensitivity in breast cancer cells (41,42). The aforementioned results of the present study indicated that the oncogene PCAT6 might be an effective therapeutic target for patients with liver cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Lv et al (40) showed that PCAT6-overexpression promotes cell proliferation, migration, invasion and reduces apoptosis through the activation of the Wnt/β-catenin pathway in cervical cancer. Other studies have demonstrated that knockdown of PCAT6 reverses chemoresistance of cancer cells to 5-fluorouracil and enhances radiosensitivity in breast cancer cells (41,42). The aforementioned results of the present study indicated that the oncogene PCAT6 might be an effective therapeutic target for patients with liver cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Our data show several lncRNAs to be upregulated in persistence cells in comparison to those in the extinction group (CBR3-AS1, RGPD4-AS1, AL356608.1, KCNMA1-AS1, SOX2-OT, LYPLAL1-AS1, AC068831.7, TMEM254-AS1, AC015849.12, and AC015849.3). Countless other studies have associated different lncRNAs to TNBC regulation, progression and even radio-sensitivity 15,[20][21][22][23] , establishing the oncogenic potential of some lncRNAs, which can serve as targets for therapeutic intervention against TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, blocking LINP1 could increase the sensitivity of the tumour‐cell response to radiotherapy in TNBC 117 . Additionally, knockdown of lncRNA PCAT6 promoted the radiosensitivity of TNBC cells through regulating miR‐185‐5p/TPD52 axis 118 . Taken together, these studies evoke the potential of altering lncRNAs expression in future to represent a novel therapeutic approach to reverse drug resistance or radiotherapy resistance in TNBC patients.…”
Section: Roles Of Lncrnas In Tnbcmentioning
confidence: 81%